Conceptual Aspects regarding the Materiality Threshold for Financial Statements as a Whole - Balan, Igor (The Journal of Accounting and Management, 2022)
One of the factors that determines the appropriateness and reasonableness of the auditor’s opinion on the financial statements as a whole is the significance of the misstatements. Entity-specific circumstances are considered essential in the audit when they significantly influence the authenticity of the client’s financial statements. Reasonable insurance is a high level of insurance. It is obtained when the auditor has obtained sufficient adequate audit evidence to reduce the risk of expressing an inadequate opinion when the financial statements are materially misstatement. An important step in the process of using the concept of significance threshold is the distribution of the preliminary value of the significance threshold. This article outlines some approaches to determining the level or levels of significance thresholds that will be applied to financial statements as a whole, with a focus on the simplest - the deductive approach, which avoids situations where the sum of significance levels for different accounts exceeds the allowable level for the entire financial reporting.